(untitled) (National Administration Journal, 2020)
This article aims to analyze the discussions that societies have been developing nowadays regarding the definition about the application of their available economic resources in highly technological investments that prioritize the increase of the economy’s productivity and competitiveness or that prioritize social investments that reduce the existing income and labor disparities. The paper investigates the characteristics of technological progress and its impacts on labor structuring, the particularities of the new technological paradigm denominated “Industry 4.0” and its reflections in labor markets, and finally the discussions on the forms of development through the so-called Appropriate Technology and Social Technology, as a prioritization to mitigate the negative repercussions of the technological advance on the labor market.